Justice through retributivism in Zhou Haohui’s death notice - Mun Chung, Lee; Awang, Mohammad Ewan; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia, 2024)
Chinese fiction has long explored the notion of retributive justice as the dominant mode of discussing socio-political issues in Chinese literature. Despite its significance, this topic has received limited scholarly attention. This article addresses this gap by analysing Zhou Haohui's novel Death Notice (2019), in which the protagonist navigates a lawless society, seeking to address the absence of justice through retributive means. Tension arises when he tries to punish the wrongdoers through retributive means to redress the lack of justice in the novel. Death Notice serves as a compelling commentary on contemporary issues in China, underscoring the urgent need for societal change. Using Goran Duus-Otterström’s retributive concepts as a lens, this paper examines Death Notice as a novel that unravels the weaknesses in the Chinese justice system. As the powerless continue to be oppressed, retributivism becomes increasingly appealing as the channel to seek justice due to its ability to accommodate the desire to seek justice. This article argues that the oppressed protagonist is acting as a retributivist to voice out the flaws in the justice system. It highlights the overlooked aspects of retributive justice in Chinese fiction and emphasises its significance as a tool for critique and the need for a more equitable society. By unravelling the complexities of justice through the protagonist's actions, this study contributes to our understanding of justice and its portrayal in Chinese literature.